Kredensial Tenaga Medis di Fasilitas Kesehatan Tingkat Lanjut di Indonesia - Sugondo Sugondo; Zuhriyatus Saidah; Esti Aditya Dewi; M. Khoirul Anwar; Novy Trianasari; Mira Veranita (Syntax Idea)
Cases of failed credentialing processes, as seen in the case of fake doctors, demonstrate the need to evaluate and improve the credentialing system in hospitals. In this context, this research will examine the role and implementation of credentials in measuring and ensuring the competency of medical staff in hospitals in Indonesia. This research aims to provide a better understanding of the effectiveness and challenges in implementing credentialing in Indonesian hospitals. In addition, it is hoped that the results of this research can provide recommendations for improving and strengthening the credentialing system to improve the quality of medical services and patient safety in hospitals.